STUDI PERFORMA MEKANIK AWAL BETON GEOPOLIMER BERBASIS FLY ASH TIPE C DI BAWAH PAPARAN SULFAT - Hazen Masrafat; Almutahir (Jurusan Teknik Sipil, Fakultas Teknik, Universitas Negeri Gorontalo, 2026)
This study examines the early-age sulfate resistance of Class C fly ash–based geopolymer concrete (GPC) in comparison with Portland cement concrete (PCC). The research evaluates mechanical performance, mass stability, and microstructural responses after 28 days of exposure to a 5% magnesium sulfate solution. The experimental program includes material characterization, dry-mix geopolymer preparation, sulfate immersion testing, and mechanical assessments. Chemical analysis shows that the fly ash contains 65% total pozzolanic oxides and 69.68% amorphous content, confirming its high reactivity and suitability for geopolymerization. The results indicate that GPC exhibits significantly better sulfate resistance, with a minimal mass change of only +0.03%, compared with PCC, which shows a +0.72% increase due to higher sulfate penetration. Mechanically, GPC demonstrates notable improvements: compressive strength increases by 25%, and elastic modulus rises by 9–11% after exposure. In contrast, PCC experiences only a slight increase in strength, primarily attributed to temporary pore filling from gypsum and ettringite formation rather than genuine structural enhancement. Microstructural observations confirm the presence of sulfate reaction products on both materials; however, no cracking or structural damage is detected, and GPC maintains a more stable aluminosilicate network. These findings highlight GPC’s superior early-age durability and its potential as a sustainable and chemically robust alternative to PCC in sulfate-rich environments. The study provides new experimental insights into the short-term sulfate behavior of Class C fly ash–based GPC and recommends future long-term durability evaluations under extended exposure durations and field-representative conditions.